Love x hate: the actuality of Paulo Freire’s thoughts and the restlessness of neofascists in Brazil - Gehlen, Maria Eloá (2020)
This article reflects the actuality of Paulo Freire’s ideals and its opposition to the neofascism movement in Brazil in this early 21st Century. Why such hate when Freire’s words lead to love? This paper aims to clarify the feeling of restlessness that Freire’s educational concepts, ideals, pieces, and practices cause in his extreme right-wing opposers. The methodology consists of two life stories with a Freireana teacher and an individual who supported the Italian fascism when he was young and lives in Brazil today. Also, a bibliographic review was held for this article. The results point to the lack of knowledge on Freire’s work by those who criticize him, as well as the unveiling of people who identify themselves with fascism ideals as people who feel intellectually inferior and, thus, cultivate hate. A factor that brings hope to the society is the emergence of antifascist movements, the responsible for public manifestations of popular social movements and the Antifa movement.